Determination of Marriage Dispensation at Gorontalo Religious Court in Accordance with the Child Protection Law No. 35 of 2014 - Hidayat, Hidayat; Wantu, Fence M.; Ahmad, Ahmad (Estudiante Law Journal, 2024)
This study examines marriage dispensation at the Gorontalo City Religious Court through the lens of Law No. 35/2014 on Child Protection. Marriage dispensation, while rooted in Indonesia's religious and cultural norms, often conflicts with the Child Protection Law, which prohibits child marriage and sets strict exceptions. Using qualitative methods, including document analysis and interviews with court officials and stakeholders, the study found discrepancies between court practices and legal provisions. Socio-cultural factors such as traditions, economic pressure, and the role of religious leaders influence dispensation decisions. Furthermore, limited understanding of child protection laws among court officials exacerbates these issues. The research highlights challenges in aligning religious and national laws and their implications for children's rights. It recommends training for court officials, clear operational guidelines, and stronger collaboration between religious and government institutions to ensure marriage dispensation aligns with child protection objectives in Gorontalo City.